Handling of Radical Prostatectomy Specimens: Total Embedding with Large-Format Histology. (10th July 2012) - Montironi, Rodolfo; Lopez Beltran, Antonio; Mazzucchelli, Roberta; Cheng, Liang; Scarpelli, Marina
Abstract : A problem when handling radical prostatectomy specimens (RPS) is that cancer is often not visible at gross examination, and the tumor extent is always underestimated by the naked eye. The challenge is increased further by the fact that prostate cancer is a notoriously multifocal and heterogeneous tumor. For the pathologist, the safest method to avoid undersampling of cancer is evidently that the entire prostate is submitted. Even though whole mounts of sections from RPS appear not to be superior to sections from standard blocks in detecting adverse pathological features, their use has the great advantage of displaying the architecture of the prostate and the identification and location of tumour nodules more clearly, with particular reference to the index tumour; further, it is easier to compare the pathological findings with those obtained from digital rectal examination (DRE), transrectal ultrasound (TRUS), and prostate biopsies. We are in favour of complete sampling of the RPS examined with the whole mount technique. There are reasons in favour and a few drawbacks. Its implementation does not require an additional amount of work from the technicians' side. It gives further clinical significance to our work of uropathologists.